Motivational climates, work passion, and behavioral consequences. (4th September 2022) - Zhang, Qinyun; Wang, Xiao‐Hua (Frank); Nerstad, Christina G. L.; Ren, Hantao; Gao, Ruoyu
Summary: Drawing on achievement goal theory and the dualistic model of passion, this study identifies (1) mastery versus performance climate as the contextual antecedent for harmonious versus obsessive passion, respectively, and (2) proactive versus pro‐job unethical behavior as the outcome of harmonious versus obsessive passion, respectively. Results from two studies—a survey study with 259 leader–subordinate dyads and an experimental study with 174 part‐time master's‐level students—largely supported our theoretical model. First, employees develop harmonious passion when they perceive the presence of a mastery climate, but develop obsessive passion when they perceive the presence of a performance climate. Second, harmonious passion mediates the positive effect of mastery climate on employees' proactive work behavior, whereas obsessive passion mediates the positive effect of performance climate on employees' pro‐job unethical behavior. Theoretical contributions and practical implications are also discussed.